Aplicación del régimen simplificado para emprendedores. - Perez Robles, Douglas Joel; Medina Celi, Katty Yasmin (Machala : Universidad Técnica de Machala, 2022)
Our work was prepared to analyze the Application of the Simplified Regime for Entrepreneurs. Tax reform came into effect on January 1, 2022, and that was created through the Organic Law for Economic Development and Fiscal Sustainability after the COVID19 Pandemic. According to the tax reform, taxpayers who comply with the requirements imposed by this Law, must be subject to the obligation and compliance with the said regime as the case may be, with regard to the Camaronera owned by Mr Dalton Montesdeoca Moreno, which is the object of study, due to his economic income ex officio, he belongs to the Rimpe Emprendedores regime, for which reason he must comply with several obligations, such as making use of electronic invoicing in a mandatory manner, presenting his tax obligations on a semi-annual basis in the that refers to VAT and annually what corresponds to Income Tax. The method that was applied for the elaboration of the research work was descriptive, which helped to solve the problems raised within the Camaronera Object of study, a qualitative approach and positivist paradigm were presented that allowed to analyze and interpret the current regulations, the method of closed interviews and data collection that was provided by the taxpayer was applied. The analysis of the results was determined based on the research provided, which generated results that demonstrate the knowledge of the application of the Rimpe entrepreneurial regime, and the incidence that it generated in the Tax obligations, which was essential to be able to issue conclusions and recommendations. in favour of the shrimp company.
Nuestro trabajo se elaboró con la finalidad analizar la Aplicación del Régimen Simplificado para Emprendedores. Reforma tributaria que entró en vigencia desde el 1 de enero de 2022, y que se creó a través de la Ley Orgánica para el Desarrollo Económico y Sostenibilidad Fiscal tras la Pandemia COVID19. Según la reforma tributaria, los contribuyentes que cumplan con los requisitos impuestos por esta Ley, se deberán sujetar de obligación y cumplimento a dicho régimen según sea el caso, en lo que respecta a la Camaronera de propiedad del señor Dalton Montesdeoca Moreno, la cual es objeto de estudio, por sus ingresos económicos de oficio pasa a pertenecer al régimen Rimpe Emprendedores, por lo que debe cumplir con varias obligaciones , como la de acogerse a la Facturación electrónica de manera obligatoria, la de presentar sus obligaciones tributaras de manera semestral en lo que refiere a IVA y de manera anual lo que corresponde al Impuesto a la Renta. El método que se aplicó para la elaboración del trabajo de investigación fue carácter descriptivo, el cual ayudo a resolver los problemas suscitados dentro de la Camaronera Objeto de estudio, se presentó un enfoque cualitativo y de paradigma positivista que permitió analizar e interpretar las normativas vigentes, se aplicó el método de entrevistas cerradas y recopilación de datos que fueron proporcionados por el contribuyente. El Analís de los resultados se determinó en base a la investigación proporcionada, lo que genero resultados que demuestran el conocimiento de la aplicación de régimen Rimpe emprendedor, y la incidencia que generó en las obligaciones Tributarias, lo que fue fundamental para poder emitir conclusiones y recomendaciones en favor de la empresa camaronera.
Keywords: SRI; REGIMEN RIMPE; EMPRENDEDOR; CODIGO TRIBUTARIO